👤
Emilynunpu
a fost răspuns

Calculați, folosind factorul comun
a) 93•67+93-89–93•145 =
b) 2+4+6+8+. . . . . . .+98 =


Răspuns :

Răspuns:

[tex]a)93 \times 67 + 93 \times 89 -93 \times 145 \\ = 93(67 + 89 - 145) = 93 \times 11 \\ = 1023 \\ b)2 + 4 + 6 + 8 + ... + 98 = \\ 2(1 + 2 + 3 + 4 + 5 + ..... + 49 \\ = 2 \times \frac{(1 + 49) \times 49}{2} \\ = 50 \times 49 = 2450[/tex]

Răspuns: Ai rezolvarea mai jos

Explicație pas cu pas:

[tex]\bf ~a) ~~93\cdot 67+93\cdot 89-93\cdot 145 =[/tex]

[tex]\bf ~~93\cdot (67+89)-93\cdot 145 =[/tex]

[tex]\bf ~~93\cdot 156-93\cdot 145 =[/tex]

[tex]\bf ~~93\cdot (156-145) =[/tex]

[tex]\bf ~~93\cdot 11 = \red{\underline{~1~023~}}[/tex]

======================

[tex]\bf b) ~~2+4+6+8+. . . . . . .+98 =[/tex]

[tex]\bf 2\cdot (1+2+3+4+5+.....+49) =[/tex]

[tex]\bf 2\cdot [(1+49)\cdot 49]:2 =[/tex]

[tex]\bf 2\cdot 50\cdot 49:2 =[/tex]

[tex]\bf 50\cdot 49 = \purple{\underline{~2~450~}}[/tex]

Bafta multa !